Halide Anion Triggered Reactions of Michael Acceptors with Tropylium Ion. Issue 4 (4th December 2019) - Hussein, Mohanad A.; Tran, Uyen P. N.; Huynh, Vien T.; Ho, Junming; Bhadbhade, Mohan; Mayr, Herbert; Nguyen, Thanh V.
Abstract: Tropylium bromide undergoes noncatalyzed, regioselective additions to a large variety of Michael acceptors. In this way, acrylic esters are converted into β‐bromo‐α‐cycloheptatrienylpropionic esters. The reactions are interpreted as nucleophilic attack of bromide ions at the electron‐deficient olefins and the approach of the tropylium ion to the incipient carbanion. Quantum chemical calculations were performed to elucidate the analogy to the amine‐ or phosphine‐catalyzed Rauhut–Currier reactions. Subsequent synthetic transformations of the bromo‐cycloheptatrienylated adducts are reported. Abstract : The tropylium ion adds to electron‐deficient olefins in a new reaction triggered by halide ions. Tropylium bromide undergoes noncatalyzed, regioselective additions to a large variety of Michael acceptors, converting acrylic esters into β‐bromo‐α‐cycloheptatrienylpropionic esters. Quantum chemical calculations elucidated the analogy to the amine‐ or phosphine‐catalyzed Morita–Baylis–Hillman and Rauhut–Currier reactions.